Overcoming barriers: Teaching english in a vulnerable context (2023)
This report talks about my journey as an English teacher at Un Nuevo Comienzo Foundation (FUNCO). With this report the idea is to show the goals, expectations, duration, and responsibilities of my role, while also focusing on my personal motivations, challenges faced, and overall growth. Through this report, I aim to reflect on the experiences learned, share my new learnings into the educational and community context, discuss teaching philosophy, and highlight the way of personal and professional development.